Influence of the antiphase domain distribution on the magnetic structure of magnetite thin films - SHVETS, IGOR; MURPHY, SHANE (American Institute of Physics, 2006)
A long-range ordered magnetic domain structure was found in magnetitelike (Fe3??O4, ? ? 0.03) thin films prepared by molecular beam epitaxy on MgO (100) substrates. The stripelike magnetic domain structure arising after suitable postprocessing differs significantly from earlier observations. The field-dependent domain structure was investigated by magnetic force microscopy in external magnetic fields. The magnetic domain structure results from a moderate perpendicular anisotropy. The domain structure is pinned, and the pinning centers arise from the magnetite antiphase domain structure.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; thin films